Da’wah Strategy through Google Search Engine Optimization - Rahmat Saputra; Ummi Habibatul Islamiyah (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2019)
There is a lot of 'junk' on the internet today that spreads radicalism, terrorism, and pornography. Da'wah in this era of internet has a big challenge in society. Everyone can access the Internet quickly, and Google search engines play a significant role in providing information. Any information will appear in the search engine, whether it is positive or negative information, that's why the preachers need to use search engine optimization for da'wah purposes. Without the right strategies, da’wah through Google search engine optimization will not succeed. The objective of this study was to explain the da’wah strategy through Google search engine optimization. This research applied library research. The results showed that the da’wah strategy through Google search engine optimization are: focus on target audience, learn what audience needs, categorized keyword for SEO, SEO analysis on website, create mobile-friendly website, use targeted keywords in page titles, use infographics, use related keywords in content, link content to external sites with high domain authority, update old content periodically, increase site speed & improving user experience. The results of this study can be used as a guideline by the preachers, Islamic practitioners both individual and institutional, as well as the entire Muslim community who want to make da’wah through Google search engine optimization successfully. DOI: https://doi.org/10.5281/zenodo.3236457